(untitled) (ENTHYMEMA, 2019)
Unnatural narratology is one of the most interesting proposals in today’s narratological landscape. “Unnatural Narratives, Unnatural Narratology: Beyond Mimetic Models”, by J. Alber, S. Iversen, H. S. Nielsen e B. Richardson, offers an initial understanding of this perspective, while the introduction aims to further enlarge the discourse in light of its most recent developments.